2011
DOI: 10.1021/ja201415j
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Crystal-Face-Dependent TiO2 Photocatalysis from Single-Molecule Imaging and Kinetic Analysis

Abstract: According to the concept of active sites, the activity of heterogeneous catalysts correlates with the number of available catalytic sites and the binding affinity of the substrates. Herein, we report a single-molecule, single-particle fluorescence approach to elucidate the inherent photocatalytic activity of exposed surfaces of anatase TiO(2), a promising photocatalyst, using redox-responsive fluorogenic dyes. A single-molecule imaging and kinetic analysis of the fluorescence from the products shows that react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
529
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 598 publications
(553 citation statements)
references
References 54 publications
19
529
2
3
Order By: Relevance
“…Over long times, the two ends of the nanorod are more productive than the middle, although the two ends are not equally active. This heterogeneous distribution of reactivity or active sites on single nanocatalysts has been extensively observed in other single-nanocatalyst systems (2,4,9,11) and is in agreement with a recent report on 1D SiO 2 -coated Au nanorods (2).…”
Section: Significancesupporting
confidence: 92%
See 2 more Smart Citations
“…Over long times, the two ends of the nanorod are more productive than the middle, although the two ends are not equally active. This heterogeneous distribution of reactivity or active sites on single nanocatalysts has been extensively observed in other single-nanocatalyst systems (2,4,9,11) and is in agreement with a recent report on 1D SiO 2 -coated Au nanorods (2).…”
Section: Significancesupporting
confidence: 92%
“…Furthermore, the wide-field imaging format of our approach offers the capability to study multiple nanorods in the same frame, thus providing higher data collection efficiency. Similar imaging techniques have also been used in long-time-averaged analyses to differentiate catalysis on different facets of metal hydroxide and oxide microcrystals (6,9,12), resolve catalytic domains (13), and map static spatial patterns of reactivity (2,4).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Liu et al reported that the photoreactivity of (010) facets of TiO 2 is higher than that of the (101) facets, while the (001) facets showed the lowest photoreactivity [116]. However, more recent research has suggested that different facets may play different roles in photoreaction [117,118].…”
Section: Anatase Tiomentioning
confidence: 99%
“…Thus, certain facets of a semiconductor prefer reduction while others favour oxidation [18][19][20] . However, reports on the reduction and oxidation reaction facets on the same semiconductor crystal (such as TiO 2 ) were often contradictory in the literature [21][22][23][24][25][26] . For example, it was reported that rutile {011} and anatase {001} faces provided the sites for oxidation, while the rutile {110} and anatase {101} faces offered the sites for reduction 24 .…”
mentioning
confidence: 99%